Tracunhaém: a tradição e memórias no moldar do barro. - Camargo, Juliano Leal (2018)
This dissertation's objective is to analyze the relations between memory and identity starting from the study of a community of artisans, inhabitants of the city of Tracunhaém, Wood Zone of the Pernambuco state - Brazil. In this manner, it is possible to approximate an empirical analysis about local craftsmanship to a theoretical referential capable of supporting the perception of the molding of clay, of Tracunhaém's urban identity, and its masters/artisans, those being prominent in this research: they are producers of symbolic goods, points of reference in the thinking of urban identity of Tracunhaém as a city also inserted in an artisan memory of sorts, serving to the establishment of a tradition. Simultaneously to the dissertation, a product in the form of an e-book was elaborated, as a means of collaborating with the visibility of the artisanal production in Tracunhaém.